2016
DOI: 10.1038/nrn.2016.28
|View full text |Cite
|
Sign up to set email alerts
|

Keep off the grass? Cannabis, cognition and addiction

Abstract: In an increasing number of states and countries, cannabis now stands poised to join alcohol and tobacco as a legal drug. Quantifying the relative adverse and beneficial effects of cannabis and its constituent cannabinoids should therefore be prioritized. Whereas newspaper headlines have focused on links between cannabis and psychosis, less attention has been paid to the much more common problem of cannabis addiction. Certain cognitive changes have also been attributed to cannabis use, although their causality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
285
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(307 citation statements)
references
References 209 publications
10
285
1
11
Order By: Relevance
“…Possible consequences of use include dependency, cognitive impairment and increased risk of psychotic illness 2 . However, most people who try cannabis do not experience prolonged adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Possible consequences of use include dependency, cognitive impairment and increased risk of psychotic illness 2 . However, most people who try cannabis do not experience prolonged adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The main possible adverse effects associated with cannabis use are dependence, cognitive and educational impairment and psychosis 22 . Crucially, evidence suggests that the incidence of adverse consequences of cannabis use is associated with the amount of THC and CBD it contains.…”
Section: The Significance Of Cbdmentioning
confidence: 99%
“…There has been considerable debate regarding whether the use of cannabis may have lasting negative effects on memory functioning, intelligence and other aspects of cognition in the normal population 22 . A recent study across three large samples found that cannabis use before the age of 17 was related to lower rates of high-school completion and degree attainment 50 .…”
Section: Cognition and Intelligencementioning
confidence: 99%
“…Studying the child-youth population is important because early onset of use (before age 15), associated with chronic use in young people increases cognitive impairment in executive and neurocognitive functions (Curran et al, 2016;Fontes et al, 2011), and may be associated with the development of dependency in adulthood (Gonzalvo, Barral, Grau-López, Esteve, & Roncero, 2011). This high use may be partly due to the fact that people tend to consider this drug as one of the least harmful in the short and long term, compared with other substances.…”
Section: Introductionmentioning
confidence: 99%